The Neuromuscular Effects of the Copenhagen Adductor Exercise: A Systematic Review - Morgan Schaber; Zachary Guiser; Logan Brauer; Rebecca Jackson; John Banyasz; Ryan Miletti; Amy Hassen-Miller (International Journal of Sports Physical Therapy)
# Background